The alloying effect and AgCl-directing growth for synthesizing a trimetallic nanoring with improved SERS. Issue 48 (26th October 2015) - Han, Shuhua; Zhou, Guangju; Fu, Yunzhi; Ma, Ying; Xu, Li; Zou, Chao; Chen, Wei; Yang, Yun; Huang, Shaoming
Abstract : We report the synthesis of high quality trimetallic Au/Ag/Pt nanorings (TAAPNs) by using Au/Ag alloy decahedra (AAAD) as templates. Abstract : We report the synthesis of high quality trimetallic Au/Ag/Pt nanorings (TAAPNs) by using Au/Ag alloy decahedra (AAAD) as templates. The alloying effect and AgCl-directing growth have been investigated in detail during the formation of TAAPN. It was found that the doping of Ag in AAAD changes the surrounding environment of Au atoms and decreases the oxidization reduction potential (ORP) of [AuCl2 ] − /Au because of the alloying effect, resulting in the dissolved O2 molecules that serve as an effective etchant for oxidizing Au to Au(i ). Ascorbic acid (AA) and chloroplatinic acid (H2 PtCl6 ) are weak acids which can accelerate the etching by increasing the concentration of H + . The AgCl selectively absorbs on {100} of the decahedra and induces the preferential deposition of H2 PtCl6 here via their complexing interaction. AA reduces Pt(iv ) and Ag(i ) to atoms which grow on {100} facets. The formed Pt/Ag layer changes the etching direction from along [100] to [111] and generates the TAAPN. Besides, it has been noted that the TAAPNs exhibit good Surface Enhanced Raman Scattering (SERS) performance.